Digital Platform-Based Learning Innovation in Elementary Schools in The Industry 4.0 Era: Systematic Literature Review - Irhamni, Hadi; Ashari, Muhammad Khakim (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Information and communication technology advances have been utilized in many sectors of human life, including educational practices. This study aims to reveal the innovation practices of app-based digital application platforms. This research was conducted using a systematic literature review (SLR) approach. Data sources come from research journal articles and books by the theme of the discussion. The data analysis technique uses content analysis. The finding or result of this research is that learning can utilize digital platform features as part of learning innovation. Digital platforms that can be utilized are such as Microsoft Teams and Edmodo applications. Both applications have many services, such as video conferencing, presentations, assignments, and online assessments. The utilization of digital platforms in schools in the Industrial Age 4.0 aligns with the development and challenges of the rapidly changing times. Digital platforms are part of the innovations that can be used as alternative media and real solutions for technology-integrated learning. Learning with digital platform media can increase student participation and collaboration and provide new, in-depth learning experiences.